Correction: Gas induced conversion of hybrid perovskite single crystal to single crystal for great enhancement of their photoelectric properties. Issue 45 (10th November 2017) - Ju, Dianxing; Zhao, Tianyu; Dang, Yangyang; Zhang, Guodong; Hu, Xiaobo; Cui, Deliang; Tao, Xutang
Abstract : Correction for 'Gas induced conversion of hybrid perovskite single crystal to single crystal for great enhancement of their photoelectric properties' by Dianxing Ju et al., J. Mater. Chem. A, 2017, DOI: ; Web:10.1039/c7ta07413a .